An Analysis of Slang Words Used in NCT 127 Song “Regular English Version” on Album Regular-Irregular - Alfiana, Dewi Rizka Nur (English Edu: Journal of English Teaching and Learning, 2025)
This study was aimed to investigate slang words formation in the NCT 127 song lyrics titled “Regular English Version” on Album Regular-Irregular. The researcher used theory of word formation process by George Yule. Descriptive qualitative research design is used as the methodology of this research. In collecting the data, the researcher used three steps which are finding, analysing, and discussing. In analysing the data, the researcher used document analysis by Bowen to interpret the meaning. The result showed there are 19 data categorized in 9 types of word formation process. Those are compounding (4 data), conversion (1 word), blending (1 word), abbreviation (1 word), clipping (4 word), borrowing (1), onomatopoeia (2 words), cliticization (4 words), coinage (1 word).